Epidermal Structure and Leaf Stomata of Several Accessions of Banana Plants (Musa spp.) - Gebiana Nyainleta; Anneke Pesik; Adriana Hiariej (Postgraduate, University of Mataram, 2022)
This study aimed to determine the structure of epidermal cells and leaf stomata in Jarum, Merah, Tanduk, Kepok, and Pei or wild banana. The type of research used was quantitative to calculate the number of epidermis, epidermal cell size, number of stomata, and stomata index. Meanwhile, qualitatively described the structure of epidermal cells, epidermal cell shape, stomata shape, and stomata type of banana leaves based on the longitudinal incision method. The results showed that four accessions of bananas have epidermal cell shapes: rectangular, pentagon, hexagon, heptagon, octagonal, and regularly length. Meanwhile, Merah have different epidermal cell shapes, namely rectangular, pentagon, hexagon, and irregular, with untidy arrangements. The stomata of the five samples are surrounded by four to six subsidiary cells and are kidney-shaped. Based on the location of the leaf surface, stomata in five banana accessions have an amphistomatic type. Pei or wild bananas have a long epidermal size compared to the other four species but have a small number of epidermis. Then, the number of stomata in all banana species differs on the upper and lower surfaces. The number of stomata is more on the lower surface of the leaves. Stomata index in all banana species is low